2011
DOI: 10.5897/ajbx11.023
|View full text |Cite
|
Sign up to set email alerts
|

Use of phosphates in meat products

Abstract: Phosphates offer a range of possibilities when used in meat and poultry productions. Food grade phosphates are used in meat products for several reasons such as changing and/or stabilizing of pHvalue, increasing water holding capacity in order to lead to higher yields, decreasing losses of weight in cooking, improving texture and sensory properties (tenderness, juiciness, color and flavor), extending shelf-life, etc. In addition, phosphates in meat products are also sources of the supply of phosphorus for cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…This led to an increase in water retention capacity, and an avoidance of deformations in the final structure of the sausage. This situation allowed to emulsify more fat, which is expressed in the uniformity of the physical structure of the product [38,44]. Several authors have related the effect of the increase in values of textural variables in meat products to the increase in the amount of phosphate [60][61] Considering the behavior of each response surface and that T4 treatment represents the typical addition values of NaCl and TPPNa for standard frankfurter sausages, it was found that T6 treatment was similar in the variables of cooking losses and textural characteristics (represented by hardness, cohesiveness and chewiness), and it had lower sodium concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to an increase in water retention capacity, and an avoidance of deformations in the final structure of the sausage. This situation allowed to emulsify more fat, which is expressed in the uniformity of the physical structure of the product [38,44]. Several authors have related the effect of the increase in values of textural variables in meat products to the increase in the amount of phosphate [60][61] Considering the behavior of each response surface and that T4 treatment represents the typical addition values of NaCl and TPPNa for standard frankfurter sausages, it was found that T6 treatment was similar in the variables of cooking losses and textural characteristics (represented by hardness, cohesiveness and chewiness), and it had lower sodium concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium and potassium salt combinations (NaCl, TPPNa, KCl and TTPK) were selected, and values were established for each one taking into account the typical level of NaCl in a sausage according to a standard formulation of 1.8% to 2.3% NaCl, replacing a maximum of 50% with (KCl), as found in other studies [38] and based on the maximum allowed values of phosphates according to the norm NTC 1325 of 2008 [39] and it was defined as being a 0% to 0.5% polyphosphate range.…”
Section: Selection Of Sodium and Potassium Salt Combinationsmentioning
confidence: 99%
“…On the one hand, tenderness and water holding capacity decrease (9). The formation of the actomyosin complex necessitates the use of phosphate, releasing the bonds between actin and myosin, in the production of many processed meat products (11,12). On the other hand, pH decline and other changes in intracellular conditions activate enzymes responsible for tenderization and formation of aroma precursors, as discussed below.…”
Section: Post-mortem Metabolismmentioning
confidence: 99%
“…Since phosphates could reduce oxidative changes of meat products by chelating with the metal ions and the removal of catalysts that initiate lipid oxidation (Long et al, 2011;Sebranek, 2009), evaluating the effects of phosphate substitutes on oxidative stability is a further point that should be discussed. Lipid and protein oxidation of restructured steaks during frozen storage is presented in Figure 4a, brines and found that lipid oxidation was higher for DBP steaks.…”
Section: Lipid and Protein Oxidationmentioning
confidence: 99%
“…In today's modern world, changes in consumer habits have led to intense demand for readyto-eat poultry products. One of those products is restructured muscle foods, that are small pieces of meat reformed into steaks, chops, and/or roast-like meat products (Long, Gál, & Buňka, 2011), allowing to develop new formulations, and presents advantages including more accurate portion control, lower cook loss, uniformity of color and texture (Farouk, 2002;Serrano, Cofrades, & Jiménez-Colmenero, 2006). The traditional process of restructured meats requires added salts to extract soluble proteins for meat binding (Lu & Chen, 1999).…”
Section: Introductionmentioning
confidence: 99%